Effects of iron limitation on photosynthesis and carbohydrate metabolism in the Antarctic diatom Chaetoceros brevis (Bacillariophyceae) - van Oijen, T; van Leeuwe, MA; Gieskes, WWC; de Baar, HJW (European Journal of Phycology, 2004)
Iron, one of the structural elements of organic components that play an essential role in photosynthesis and nitrogen assimilation of plants, is available at extremely low concentrations in large parts of the Southern Ocean's surface waters. We tested the hypothesis that photosynthesis is the primary target of iron stress in phytoplankton living in this specific environment, resulting in a reduced carbohydrate production. Cultures of a small Antarctic diatom, Chaetoceros brevis, were exposed to two different photon irradiances under iron-rich and iron-poor conditions. Under both light regimes growth rate was reduced only slightly by iron starvation, as expected because the iron requirement of a small-celled species such as C. brevis is low. Even so, iron-starved cells differed markedly from iron-replete cells: for low and high irradiance, respectively, they had a 20 and 27% lower content of light-harvesting pigments (chlorophyll a and c(2) and fucoxanthin), a 8 and 15% decrease in light absorption and a 15 and 17% decrease in quantum yield of photosystem II. The diurnal production of water-extractable carbohydrates was reduced by 28 and 31%, which resulted in a low supply of energy and carbon skeletons from these storage products. This may well have influenced protein synthesis. The nocturnal consumption of carbohydrates was also reduced, which, together with the almost proportional decrease in cellular C and N content, suggests that the C and N metabolism were tightly tuned in iron-stressed cultures. The decrease in C and N content correlated with a decrease in cell volume. Our results indicate that iron limitation is likely to affect the ability of phytoplankton to maintain high rates of protein synthesis within the deep wind-mixed layer of the Southern Ocean. In addition, growth at the surface could be inhibited by too much light: iron-poor cultures of C. brevis grown at low irradiance showed enhanced sensitivity to photoinhibition.